Factors impacting the formation of 3-MCPD esters and glycidyl esters during deep fat frying of chicken breast meat - Wong, Yu Hua; Lai, Oi Ming; Abas, Faridah; Nyam, Kar Lin; Nehdi, Imededdine Arbi; Muhamad, Halimah; Tan, Chin Ping (Springer, 2017)
The effect of the frying temperature, frying duration and the addition of NaCl on the formation of 3-monochloropropane-1,2-diol (3-MCPD) esters and glycidyl esters (GE) in palm olein after deep frying was examined in this study. The eight frying systems were deep-fat frying (at 160 and 180 °C) of chicken breast meat (CBM) (with 0, 1, 3 and 5% sodium chloride, NaCl) for 100 min/day for five consecutive days. All oil samples collected after each day were analyzed for 3-MCPD ester, GE, and free fatty acid (FFA) contents, specific extinctions at 232 and 268 nm (K 232 and K 268), p-anisidine value (pA), and fatty acid composition. There was a significant (p < 0.05) decrease in the 3-MCPD esters and a significant (p < 0.05) decrease in the GE with the increasing of the frying duration. There were significant (p < 0.05) increases in the 3-MCPD esters formed when the concentration of NaCl increased from 0 to 5%. The addition of NaCl to the CBM during deep frying had no significant effect on the GE generation. The FFA contents, K 232 and K 268 and pA showed that all the frying oils were within the safety limit.